Perancangan Program Aplikasi Geometri Peledakan Tambang Terbuka Berbasis Mobile Menggunakan Bahasa Pemrograman Android Studio - Reynaldi Ezra; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. At this time Mining Industrial have entered the era where the Industrial Revolution 4.0. Certainly we have to following to apply the concept of automation carried out by machines without the need for human power in its application. It is needed in the industry for saving time, energy and cost efficiency.Especially in the implementation of blasting, we certainly need high accuracy and time efficiency to calculate very complicated geometries if manual calculations and certainly have an important role in the success of blasting to achieve the target blasting Fragmentation.To support technological advances in the Industrial Revolution Era 4.0, especially in the Blasting tecnique so that it is easy to calculate the blasting geometry and fragmentation produced, in this research, a Mobile-based Geometry and Fragmentation Blast application is made using the Android Studio, where almost everyone currently has Android Smartphone technology.The making of this application program uses 2 geometries namely R.L.Ash and C.J.Konya where both methods are often used as a basis for calculating blasting geometry. In the application trial phase of simulation data and compared with manual calculations, the program runs well and also the percentage of errors is very low when matched with manual calculations which is only 1,38%.Keywords: Blasting, Geometry, Fragmentation, Application, Android